Negative comparative law : a strong programme for weak thought - Legrand, Pierre, 1959- (Cambridge, United Kingdom : New York, NY : Cambridge University Press, 2022)
"A critical manifesto making the case for a radically alternative approach to the theory and practice of comparative law. This fragment's argument rejects positivism, the leading theoretical framework informing comparative law, and introduces culturalism with a view to enhancing comparatism's interpretive yield"--
Raising my game : to fail better -- Sniffing the wind -- Onomastics, very briefly -- More comparative law -- Borges's challenge -- Outings -- For indiscipline -- Decoloniality -- The same as the different -- Comparatism is culturalism -- This comparatist, even -- The negative -- The negative, applied -- My equipment -- Appreciation -- Supplement.
Includes bibliographical references and indexes.
Keywords: Comparative law; Sociological jurisprudence; Law -- Philosophy; Droit compare; Sociologie juridique; Law / Comparative; Comparative law; Law -- Philosophy; Sociological jurisprudence